2011
DOI: 10.5539/elt.v4n3p232
|View full text |Cite
|
Sign up to set email alerts
|

Prospective English Language Teachers’ Perceptions of the Target Language and Culture in Relation to their Socioeconomic Status

Abstract: Prospective foreign language teachers need to have an accurate knowledge and a positive perception of the target language and target culture so that they can help their students gain further insight on culture by and large. Hence, by means of a questionnaire, prospective English language teachers' (n= 412) perceptions of the target language and culture are sought to be answered in relation to their present knowledge of the target language and culture and their socioeconomic status. The results indicate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
1
4
0
4
Order By: Relevance
“…There is a total of 116 Spanish journals with the impact factor calculated in 2010, as there are five that are in both indexes'. 3 But a scientific career is also influenced by other factors, such as professional status, gender and the cultural and structural characteristics of each institution (Arikan 2011). For example, Gu et al (2011) studied the relationship between the impact indicators and doctoral students' research, and found that the individual factors, specifically the status in academia, have significant effects on the number of publications with impact.…”
Section: Methodological Approachmentioning
confidence: 99%
“…There is a total of 116 Spanish journals with the impact factor calculated in 2010, as there are five that are in both indexes'. 3 But a scientific career is also influenced by other factors, such as professional status, gender and the cultural and structural characteristics of each institution (Arikan 2011). For example, Gu et al (2011) studied the relationship between the impact indicators and doctoral students' research, and found that the individual factors, specifically the status in academia, have significant effects on the number of publications with impact.…”
Section: Methodological Approachmentioning
confidence: 99%
“…For instance, the low socio-economic status of the district seemed to have very limited potential for professional development and especially male teachers in this study complained about the fact that they did not have as many opportunities as their counterparts in west districts of Turkey. As stated in Arikan (2011), there is a correlation between teachers' socioeconomic conditions and their perceptions of target language culture. The teachers in the current study stated this fact repeatedly during the interviews and focus groups.…”
Section: Discussionmentioning
confidence: 99%
“…Ulaşılabilen alanyazında yabancı dil öğretiminde hedef kültürün kullanılması ve kültür aktarımı bağlamında Türkiye'de yapılan bazı çalışmalara (Arıkan, 2011;Bayyurt, 2007;Belli, 2018;Kuru-Gönen & Sağlam, 2012) rastlanmakla birlikte bu çalışmaların genellikle kültür konusunu yabancı dil olarak İngilizce öğretimi bağlamında ele aldıkları ve İngilizce öğrenenlerin, öğretenlerin ya da ingilizce öğretmeni adaylarının yabancı dil derslerinde kültür aktarımına ilişkin görüşlerini belirlemek amacıyla yapıldıkları görülmektedir. Yabancı dil olarak Türkçe öğretiminde kültür ve dil ilişkisi üzerine ulaşılabilen alanyazında yapılan çalışmalara bakıldığında ise bir çalışma (Saygılı & Kana, 2018) dışında çalışmaların büyük çoğunluğunun yabancılara Türkçe öğreten kitaplarda kültür aktarımına ilişkin araştırmalar ya da yabancı dil öğretiminde kültürün rolüne ilişkin alanyazın taraması olduğu görülmektedir.…”
Section: Introductionunclassified
“…İngilizce öğretmeni adaylarının hedef dil ve hedef kültüre ilişkin görüşlerini katılımcıların sosyo-ekonomik durumları bağlamında inceleyen Arıkan (2011) çalışmasında katılımcıların kendilerini hedef dilde yetkin olarak görseler de hedef kültür açısından zayıf gördüklerini ve katılımcıların hedef dil ve kültüre ilişkin görüşlerinin ailelerin sosyo-ekonomik durumuna bağlı olarak değişiklik gösterdiklerini belirlemiştir.…”
unclassified